[PP.29.12] LINKING ULTRASOUND ASSESSMENT OF EXTRACRANIAL CEREBRAL CIRCULATION TO THE CARDIOVASCULAR AND RENAL EVENTS AT HYPERTENSIVE PATIENTS WITH OR WITHOUT METABOLIC SYNDROME. (September 2016) - Gavrila, A.; Florea, M.; Ciobanu, M.; Pritulescu, C.; Rusu, M.; Sosea, I.; Persu, R.; Rosu, A.
Abstract : Objective: The objective of the study was to estimate how the ultrasound parameters of the carotid arteries correlate with prognostic of hypertensive patients (pts) with or without metabolic syndrome (MS). Design and method: 40 hypertensive pts (mean age = 57.3 ± 7.5 years, 52.5% males)-group1 and 40 hypertensive pts with MS, matched for age and sex (mean age = 58.6 ± 7.4 years, 55% males)-group2. Vascular ultrasound parameters performed were: thickness of intima-media layer (IMT) in common carotid arteries (CCA), peak systolic velocity (PSV) in internal carotid arteries (ICA), end diastolic velocity (EDV) in ICA, resistance index (RI) in ICA, peak systolic velocity ratio (PSVR) in ICA and CCA. All pts were evaluated during one year in order to detect the following complications: unstable angina (UA), non-ST-segment-elevation myocardial infarction (NSTEMI), transient ischemic stroke (TIS), ischemic stroke (IS), renal dysfunction (RD): microalbuminuria, proteinuria, chronic kidney disease. Results: In group1, UA was significantly associate with higher EDV in ICA (29.3 ± 2.9 cm/s vs 16.5 ± 1.8 cm/s, p = 0.03). In the same group, TIS was found in a significantly higher proportion at pts with greater IMT in CCA (1 ± 0.2 mm vs 0.4 ± 0.3 mm, p = 0.01). In group2, UA was significantly associated with a greater RI in ICA (0.75 ± 0.08 vs 0.57 ± 0.12, p = 0.02). NSTEMI was significantly more frequent in group2 pts with greater RI in ICA (0.76 ± 0.11 vs 0.56 ± 0.13, p = 0.03) and with higher PSVR in ICA and CCA (2.61 ± 0.12 vs 1.25 ± 0.2, p = 0.008). In the same group, TIS was found in a significantly greater proportion at pts with higher EDV in ICA (28.7 ± 2.6 cm/s vs 17.3 ± 2.2 cm/s, p = 0.03). RD was significantly associated with greater PSVR in ICA and CCA at hypertensive pts with MS (2.58 ± 0.19 vs 1.14 ± 0.21, p = 0.001). Conclusions: Greater IMT in CCA and higher level of EDV in ICA seem to predict a worse mid term outcome (one year) concerning cardiovascular and cerebrovascular events at hypertensive pts, especially with MS. Moreover, higher RI in ICA and greater PSVR in ICA and CCA appears to have more powerful mid term prognostic value (one year) for incidence of acute coronary syndromes without ST-segment elevation at hypertensive pts with MS. In this group, higher PSVR in ICA and CCA reflects unfavorable evolution of renal function.